1998
DOI: 10.1136/oem.55.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Human effect monitoring in cases of occupational exposure to antineoplastic drugs: a method comparison.

Abstract: Objectives-To investigate whether DNA damage increased in subjects possibly exposed to high amounts of antineoplastic agents. Methods-The level of genetic damage was determined in peripheral mononuclear blood cells with the sister chromatid exchange test, the alkaline elution technique, and the cytokinesis block micronucleus test. Results-The supposed increased exposure of the study subjects was caused by a malfunction of a safety hood resulting in leakage of air during preparation of an infusion of an antineo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…In a previous work, incorporation of antineoplastic agents by oncology personnel was detected despite standard safety precautions, such as the use of laminar airflow hoods and personal protective clothing [Pethran et al, 2003]. The importance of taking correct safety measures while occupationally handling antineoplastic drugs on the potential genotoxic risk has been revealed in several studies that analyzed individuals with different degrees of protection: the more protective measures were taken, the less genotoxic damage was observed [Oestreicher et al, 1990;Fuchs et al, 1995;Brumen and Horvat, 1996;Kevekordes et al, 1998]. Thus, our data suggest that safety measures adopted by the oncology nurses analyzed are not enough to prevent health hazards related to antineoplastic drug management.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous work, incorporation of antineoplastic agents by oncology personnel was detected despite standard safety precautions, such as the use of laminar airflow hoods and personal protective clothing [Pethran et al, 2003]. The importance of taking correct safety measures while occupationally handling antineoplastic drugs on the potential genotoxic risk has been revealed in several studies that analyzed individuals with different degrees of protection: the more protective measures were taken, the less genotoxic damage was observed [Oestreicher et al, 1990;Fuchs et al, 1995;Brumen and Horvat, 1996;Kevekordes et al, 1998]. Thus, our data suggest that safety measures adopted by the oncology nurses analyzed are not enough to prevent health hazards related to antineoplastic drug management.…”
Section: Discussionmentioning
confidence: 91%
“…As reported by Kevekordes et al [6], the use of the fresh blood has an advantage of detecting acute effects on DNA, while consisting of two thirds of shortliving non-lymphocyte nuclear blood cells (i.e., monocytes and granulocytes). By contrast, the use of isolated long-living peripheral blood lymphocytes enables detection of chronic or subchronic effects in the DNA.…”
Section: Discussionmentioning
confidence: 96%
“…Various methods of monitoring biological effects have been suggested that should be considered as internal dosimeters in the detection of increased genotoxic and presumably also carcinogenic risks [6]. Among them, there are different cytogenetic techniques that provide information about damage in individual cells: detection of chromosomal aberrations, sister chromatid exchanges, and micronuclei in peripheral blood lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of signi®cant dierences in SCE between exposed probands and controls observed in our study is in good accordance with recently published data (Lanza et al 1999, Kasuba et al 1999, and may be related to the use of protective equipment at work that is expected to determine the genotoxic impact of occupational exposure to anticancer drugs. For instance, Kevekordes et al (1998) found signi®cant increases of SCEs and MN frequencies in ten nurses who were considered to be exposed to high amounts of antineoplastic agents, after malfunction of a safety hood. Elevated levels were still observed 2 months later, but had decreased to control values after 9 months.…”
Section: Discussionmentioning
confidence: 99%